(untitled) (International Journal of Innovative Technologies in Economy, 2021)
In the modern economy, the problems associated with transport logistics (TL) have become important. The strategic goal of the TS is to increase the level of competitiveness of firms in the market, as a result of which, TL is that special direction of the economy, which will contribute to the growth of its level of efficiency and lead to high commercial results. A consistent assessment of the effectiveness of the functioning of the enterprise’s TL is a guide to its activities, since the results of the assessment help managers to identify complex components of the system and make optimal management decisions. All this leads to the need to develop assessment mechanisms that will help to calculate the level and degree of efficiency of the TL functioning, because modern assessment methods do not make it possible to identify the integral level of TL efficiency based on the TL efficiency levels. Consequently, the development of a systematic assessment of the effectiveness of TL, based on identifying the levels of efficiency of subsystems, plays a major role in finding its place in the market. A systematic approach to assessing the effectiveness of TL functioning is confirmed by a logistic approach to their management, as well as the properties they own. The significance of the research is confirmed by the fact that the development and improvement of methods for assessing the effectiveness of THB processes in a firm contributes to the implementation of specific use of theoretical provisions in the activities of commercial entities of the Republic of Azerbaijan.